Pre-harvest chemical sprays for enhancing shelf life and fruit quality of jamun (Indian Journal of Arid Horticulture, 2021)
An experiment was conducted to study the effect of different pre-harvest sprayed chemicals i.e. calcium chloride (1.0, I.SO,2.0%), GA, (50, 100 ppm), potassium sulphate (1.0,2.0%) and control (water spray) on shelf life and post harvest quality of jamun cv. Goma Priyanka at ambient temperature under semi-arid conditions of western India. Increase in physiological loss in weight (PLW), spoilage percentage and decrease in titratable acidity, ascorbic acid, total sugar and anthocyanin content with advancement of storage period were general phenomena in all the treatments. However, TSS, and TSS: acidity ratio initially increased and thereafter decreased, respectively irrespective of treatments. Minimum spoilage loss was recorded in the fruits treated withCaCl,2.0% (13.33%) closely followed by CaCI,1.50% (17.28%). Same treatment also showed lowest PLW (13.65%) on the last day of storage and exhibited 3.03daysofeconomic shelf life, while control had 1.68 days of economic shelf life under ambient conditions. Highest PLW (18.17%) and spoilage (25.34%) were recorded in the control on the last day of storage (4'"day). In general, shelf life of jamun fruits increased with the increase in concentration of calcium chloride. It may be concluded that CaCI,1.50 to2.0% can be sprayed before harvest of fruits for enhancing the shelf life and maintaining fruit quality of jamun under ambient conditions.